Krajowe mechanizmy prewencji tortur: między krajową a międzynarodową ochroną praw człowieka - Grygiel-Zasada, Joanna (PRAWO i WIĘŹ, 2025)
The paper discusses the issue of national preventive mechanisms established by states in the performance of duties imposed by the Optional Protocol to the Convention against Torture and other Cruel, Inhuman or Degrading Treatment or Punishment, adopted by the United Nations. The purpose of the study is to present specific challenges related to the establishment and functioning of institutions responsible for monitoring places of detention at the national level. These challenges stem from the unique nature of the two-pillar system of prevention established by the OPCAT, and the dualism of national preventive mechanisms, which are rooted in both international and domestic law. The author’s research is based on an analysis of four significant aspects: the wide margin of appreciation granted to states in establishing national preventive mechanisms, the obligation to guarantee the independence of mechanisms, granting access to all places of detention, and cooperation with the Subcommittee on Prevention. The study includes examples of established national preventive mechanisms and an analysis of the first general comment to OPCAT, adopted in 2024.